AUDIT FEE, JASA SELAIN AUDIT, PROFIL KANTOR AKUNTAN PUBLIK, LAMANYA HUBUNGAN AUDIT DENGAN KLIEN TERHADAP INDEPENDENSI AKUNTAN PUBLIK DI PEKANBARU DAN MEDAN - Rheny Afriana Hanif; Elwina Putri ' (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
The study was conducted using a survey method for public accounting firms in the region Pekanbaru and Medan. The study aims to find evidence of the audit fee, services beside the audit, public accountant office profile, and the duration or assignation of audit to public accountant independency. The population in the study were accountant public in Pekanbaru and Medan. Sample taken amoundted to 26 public accounting firms in Pekanbaru and Padang with 130 respondents. Types of data used are primary data by the method of data collection using questionnaire. The method of data analysis used in this study is multiple regression with the help of software SPSS version 17.00. The results showed that the use of audit fee, services beside the audit, public accountant office profile, and the duration or assignation of audit effect on public accountant independency with a significance value of 0.000, 0.030, 0.054 and 0.000. The value Alpha egual to 0.05. The value of Ajusted R squareis equal to 0.615, which means 61.5% of independent variables in the study was able to influence the dependent variable, while the remaining 38.5% is explained by other variables not included in this study, as: relation of effort with client , office public accountant size measure, etc.Kata Kunci : Audit fee, services beside the audit, public accountant profile, the duration or assignation of audit, independence.